2013
DOI: 10.5539/ies.v7n1p21
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions of Emotional and Instrumental Teacher Support: Relations with Motivational and Emotional Responses

Abstract: We explored whether students' perceptions of emotional and instrumental support provided by their mathematics teacher constitute separate dimensions of teacher support and how they are related. We also analyzed how students' perceptions of emotional and instrumental support in math lessons relate to math anxiety, intrinsic motivation, help-seeking behavior, and effort. The participants were 309 Norwegian students in 9th and 10th grade. The data were analyzed by means of structural equation modeling (SEM). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
101
1
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 64 publications
9
101
1
7
Order By: Relevance
“…This study also revealed increased engagement with mathematical tasks for highly motivated students. Other research suggests that students who have high intrinsic math motivation may also have a greater conceptual knowledge of math topics [20,34,48]. In short, previous research points toward a link between student motivation and achievement.…”
Section: Motivation and Student Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also revealed increased engagement with mathematical tasks for highly motivated students. Other research suggests that students who have high intrinsic math motivation may also have a greater conceptual knowledge of math topics [20,34,48]. In short, previous research points toward a link between student motivation and achievement.…”
Section: Motivation and Student Achievementmentioning
confidence: 99%
“…academic outcomes [16,20]. The current study details the development, piloting, and implementation of an instrument designed to measure these critical motivational constructs specifically in elementary mathematics students.…”
mentioning
confidence: 99%
“…The changes which happen in the course of professional activity and, respectively, in vocational guidance of future specialist, increase the importance of a subjective basis of a professional choice (Kargina, 2015). It reveals the problem to form early motivation of professional self-determination (Côté & Levine, 1997;Federici & Skaalvikm, 2014). At present time the interests, tendencies, requirements and abilities of students become a decisive factor while choosing one's professional activity (Kutty, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have frequently reported that student perceived teacher support is one of the factors affecting motivational beliefs (Federici & Skaalvik, 2014;Skaalvik, Federici, & Klassen, 2015;Sakiz, Pape, & Hoy, 2012;Garmezy, 1994;Pianta, 1999) and academic achievement (Federici & Skaalvik, 2014;Klem & Cornell, 2004;Pianta, 1999;Skaalvik et al, 2015). Supportive teacher-student relations in the classroom environment have been shown to influence students' self-efficacy positively (Eccles, 2007;Federici & Skaalvik, 2014;Skaalvik et al, 2015;Wentzel, 1998).…”
Section: Teacher Support and Math Self-efficacymentioning
confidence: 99%
“…Supportive teacher-student relations in the classroom environment have been shown to influence students' self-efficacy positively (Eccles, 2007;Federici & Skaalvik, 2014;Skaalvik et al, 2015;Wentzel, 1998). Teacher behavior plays an important role in motivational constructs; that is, when students perceive their teacher as supportive, they are more likely to be interested and successful in the class (Federici & Skaalvik, 2014;Lapointe et al, 2005;Wentzel, 1998). The student's perception of teacher proximity and influence is significantly associated with the student's self-efficacy for "average" and "talented" students (Lapointe et al, 2005).…”
Section: Teacher Support and Math Self-efficacymentioning
confidence: 99%